Child Language : Acquisition and Growth. - Lust, Barbara C. (Cambridge textbooks in linguistics., 2006)
Language is a skill that young children master with incredible ease and speed, and the remarkable way in which they achieve this has long fascinated linguists and developmental psychologists alike. This accessible new textbook introduces the field of child language acquisition, exploring language development from birth.